Expressing Intention Analysis on English Subject Class Students’ Speaking Ability at First Grade of SMKN 6 Padang - Suri, Elda Martha (Budapest International Research and Critics University, 2021)
The objective of this research was to find out the students’ ability and students' difficulties in expressing intention. This research was conducted at SMKN 6 Padang, the academic year 2020/2021. The researcher conducted this research based on the finding in the classroom. Many students were not able to speak well in the teaching and learning activities in the classroom. This research used descriptive quantitative research. The population in this research was 68 students first years of SMKN 6 Padang, namely first kuliner one and first kuliner two. The result of the research showed that students’ speaking ability in expressing intention was moderate. (1) The ability of students’ in pronunciation was moderate (91.42% ). (2) The ability of students’ in choosing vocabulary was moderate (94.28%). (3) The ability of students’ in fluency was moderate (85.71%). (4) The ability of students’ in using grammar was moderate (88.57%). (5) The ability of students’ in comprehension was moderate (82.85%). The researcher concluded that students speaking ability in expressing intention was moderate.